Isidro Aliau: teacher, inspector and reformist in the origins of the Argentine educational system - Baretta, Mónica (Historia y Memoria de la Educación, 2021)
In the middle of the 19th century, the progressive consolidation of the American independent states opened new debates related to the need to extend school-based education to the entire population. Within this framework, this article aims to address the figure of Isidro Aliau, a Catalan teacher exiled in Argentina who between 1876 and 1887 held the position of Inspector General of Schools in the province of Santa Fe (Argentine Republic). From there, some of his pedagogical-linguistic contributions will be presented, contributions that have received scarce attention either in the field of the history of education or in the field of language politics. The article focuses on two of his main contributions: the development of a simultaneous teaching method of reading and writing to be used in primary schools, and the presentation of a project to reform the orthography of Spanish language, whose foundation was to simplify writing as a way to facilitate learning. These contributions are interpreted as political interventions in the realm of language, insofar as they represent an attempt to affect the social distribution of the written word, within the framework of an endeavor to expand literacy and democratize education.